1996
DOI: 10.1002/eji.1830261259
|View full text |Cite
|
Sign up to set email alerts
|

Protective major histocompatibility complex genes and the role of interleukin‐4 in collagen‐induced arthritis

Abstract: To investigate the role of interleukin (IL)-4 during the triggering of collagen-induced arthritis, we examined the effects of the I-A(b) and I-E protective/suppressive genes and passively administered anti-IL-4 monoclonal antibody. In contrast to the action of I-E expression on its own, which has mainly a suppressive effect post-triggering, the combination of I-A(b) and I-E had a marked protective effect. Assuming, on the basis of previous experience with the I-A(b) allele, that it might act through suppressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
(12 reference statements)
1
20
0
Order By: Relevance
“…This issue regarding IL-4, namely a Th2 cytokine acting similarly to IL-13, seems to conflict with our data, and it is difficult to generalize these data rationally. Hesse reported that treatment with an IL-4-neutralizing antibody over a period extending over 6 days post immunization exacerbated the collagen-induced arthri- tis, but when curtailed to 2 days post immunization, the disease was reduced [24]. Anti-IL-4 antibody therapy may act in a complicated way in the course of an autoimmune disease.…”
Section: Discussion Effect Of Il-13-ig Gene Transfer On Eammentioning
confidence: 99%
“…This issue regarding IL-4, namely a Th2 cytokine acting similarly to IL-13, seems to conflict with our data, and it is difficult to generalize these data rationally. Hesse reported that treatment with an IL-4-neutralizing antibody over a period extending over 6 days post immunization exacerbated the collagen-induced arthri- tis, but when curtailed to 2 days post immunization, the disease was reduced [24]. Anti-IL-4 antibody therapy may act in a complicated way in the course of an autoimmune disease.…”
Section: Discussion Effect Of Il-13-ig Gene Transfer On Eammentioning
confidence: 99%
“…Its H2E molecule is no longer expressed, as commonly occurs in mice (36,37). The promoter at its H2Ab locus gives its H2A molecule some of functions of the missing H2E, namely high expression (23,38), and a consequent effect on Th1͞Th2 balance that affects disease susceptibility (39,40). The wild-derived inbred strains that have this type of promoter at H2Ab are CZECH, LEWES, MOR, PERC, SK, SF, TIRANO, WSB, ZALENDE, and M. caroli.…”
Section: Discussionmentioning
confidence: 99%
“…Crosses with naturally C5-deficient mice indicate that an intact C5 gene is required for the disease to develop (10). Furthermore, substitution in the MHC of a class II allele that suppresses the early burst of IL-4 production partially protects against the disease, in accordance with the need for this early burst as demonstrated by treatment of mice with anti-IL-4 monoclonal antibody (11,12).…”
mentioning
confidence: 83%